2007
DOI: 10.1111/j.1460-9568.2006.05259.x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced anxiety, depressive‐like behaviour and impaired recognition memory in mice with reduced expression of the vesicular glutamate transporter 1 (VGLUT1)

Abstract: Three isoforms of a vesicular glutamate transporter (VGLUT1-3) have been identified. Of these, VGLUT1 is the major isoform of the cerebral cortex and hippocampus where it is selectively located on synaptic vesicles of excitatory glutamatergic terminals. Variations in VGLUT1 expression levels have a major impact on the efficacy of glutamate synaptic transmission. Given evidence linking alterations in glutamate neurotransmission to various neuropsychiatric disorders, we investigated the possible influence of a d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
109
2

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 152 publications
(120 citation statements)
references
References 55 publications
6
109
2
Order By: Relevance
“…In agreement with our previous study, VGLUT1+/-mice showed normal levels of glutamate but decreased cortical and hippocampal levels of GABA and VGLUT1 as well as helpless behaviour compared to WT (17). In addition, we found here an increased synthesis of neuronal glutamate ( 13 C-4-glutamate) in whole brain extracts and a downregulation of the glial excitatory amino acid transporter 1 (EAAT1) in the frontal cortex and hippocampus.…”
Section: Regulation Of Glutamate/gaba Cycle and Behaviour By Reduced supporting
confidence: 80%
See 1 more Smart Citation
“…In agreement with our previous study, VGLUT1+/-mice showed normal levels of glutamate but decreased cortical and hippocampal levels of GABA and VGLUT1 as well as helpless behaviour compared to WT (17). In addition, we found here an increased synthesis of neuronal glutamate ( 13 C-4-glutamate) in whole brain extracts and a downregulation of the glial excitatory amino acid transporter 1 (EAAT1) in the frontal cortex and hippocampus.…”
Section: Regulation Of Glutamate/gaba Cycle and Behaviour By Reduced supporting
confidence: 80%
“…A recent study carried out in our laboratory reports that mice heterozygous for VGLUT1 (VGLUT1+/-), exhibit decreased cortical and hippocampal levels (35-45 %) of the inhibitory neurotransmitter GABA as well as helplessness in the forced swimming test (17). Here, we asked whether decreased VGLUT1 levels could be considered as a potential biological risk factor of major depression, alone and in combination with adverse environmental factors.…”
Section: Introductionmentioning
confidence: 99%
“…Hippocampal expression of VGLUT1 mRNA and protein is decreased in schizophrenia (Eastwood and Harrison, 2005;Sawada et al, 2005;Piyabhan and Reynolds, 2006) and, although striatal deficits have also been reported (Piyabhan and Reynolds, 2006;Nudmamud-Thanoi et al, 2007), cortical changes (which do occur in depression; Gilabert-Juan et al, 2012) are far less robust in schizophrenia (Corti et al, 2007;OniOrisan et al, 2008;Uezato et al, 2009;Eastwood and Harrison, 2010) and appear restricted to specific layers of the prefrontal cortex (Eastwood and Harrison, 2005;Bitanihirwe et al, 2009), whereas the amygdala remains unaffected . The principal finding of the current study is that administration of a VGLUT1-targeting lentiviral shRNA vector into the dorsal hippocampus of Targeting whole-brain VGLUT1 expression using conventional gene knockout strategies results in a 35-41% decrease in transporter levels in heterozygous animals (Tordera et al, 2007;Garcia-Garcia et al, 2009). These mice exhibit anxiety and a 'depressive-like' phenotype accompanied by deficits in working, social, and visual recognition memory and impaired PPI, reversal learning, fear extinction, and hippocampal long-term potentiation (Tordera et al, 2007;Garcia-Garcia et al, 2009;Balschun et al, 2010;Elizalde et al, 2010;Inta et al, 2012;Callaerts-Vegh et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The principal finding of the current study is that administration of a VGLUT1-targeting lentiviral shRNA vector into the dorsal hippocampus of Targeting whole-brain VGLUT1 expression using conventional gene knockout strategies results in a 35-41% decrease in transporter levels in heterozygous animals (Tordera et al, 2007;Garcia-Garcia et al, 2009). These mice exhibit anxiety and a 'depressive-like' phenotype accompanied by deficits in working, social, and visual recognition memory and impaired PPI, reversal learning, fear extinction, and hippocampal long-term potentiation (Tordera et al, 2007;Garcia-Garcia et al, 2009;Balschun et al, 2010;Elizalde et al, 2010;Inta et al, 2012;Callaerts-Vegh et al, 2013). The latter is consistent with the fact that VGLUT1 localizes to synapses with low release probability (that exhibit long-term potentiation), whereas VGLUT2 localizes to synapses with high release probability (that exhibit longterm depression; Varoqui et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Mice that carry a hemizygous knockout such that they express only half the amount of Slc17a7 compared to wild-type mice, are more anxious (Tordera et al 2007) and more vulnerable to chronic mild stress (GarciaGarcia et al 2009;Farley et al 2012). Here, the expression of Slc17a7 in brain hemispheres in rats from the tame selection line was twice that in the aggressive rats.…”
Section: Discussionmentioning
confidence: 78%